2012
DOI: 10.1530/jme-11-0061
|View full text |Cite
|
Sign up to set email alerts
|

Ormeloxifene inhibits osteoclast differentiation in parallel to downregulating RANKL-induced ROS generation and suppressing the activation of ERK and JNK in murine RAW264.7 cells

Abstract: Ormeloxifene (Orm), a triphenylethylene compound, has been established as a selective estrogen receptor modulator (SERM) that suppresses the ovariectomy-induced bone resorption in rats. However, the precise mechanism underlying the bone-preserving action of Orm remains unclear. In this study, we evaluated the effect of Orm on osteoclast formation induced by receptor activator of nuclear factor kB ligand (RANKL) in the murine macrophage cell line RAW264.7. We also explored the mechanism of action of Orm by stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The role of JNK in osteoclastogenesis has also previously been described (Cheng et al ., ; Kharkwal et al ., ). However, as with p38MAPK, intracellular signalling via this protein is secondary in our model; pJNK is activated at late time points (2–4 h) (see Supporting Information Figure S1B) and neither A 2A R activation/inhibition nor PKA silencing affected pJNK activation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The role of JNK in osteoclastogenesis has also previously been described (Cheng et al ., ; Kharkwal et al ., ). However, as with p38MAPK, intracellular signalling via this protein is secondary in our model; pJNK is activated at late time points (2–4 h) (see Supporting Information Figure S1B) and neither A 2A R activation/inhibition nor PKA silencing affected pJNK activation.…”
Section: Discussionmentioning
confidence: 97%
“…Of the three MAPKs studied here, only ERK1/2 is a target for adenosine A 2A receptor regulation. Although ERK1/2 plays a role in osteoclast survival (Miyazaki et al ., ) and differentiation (Saulnier et al ., ) our results remain controversial because prior reports document that different treatments such as bisphosphonates and statins (Tsubaki et al ., ) or ormeloxifene (Kharkwal et al ., ) exert their inhibitory action through inhibition of this MAPK. In contrast, we found that the A 2A R ligation both stimulated ERK 1/2 activation and inhibited osteoclast differentiation in a PKA‐dependent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen is essential to bone health for its antioxidant activity in osteoclasts and stimulating effects on osteoblasts (Kharkwal et al, 2012; Dou et al, 2016). Postmenopausal osteoporosis is a disease characterized by excessive bone destruction, which is a result of estrogen deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…We find that NLRP3 assembles a functional inflammasome in WT and mutant pre‐OCs and OCs in the absence of proinflammatory LPS‐priming signals and exogenously added ATP. Although inflammasome‐activating signals may be dispensable for mutant cells, RANKL‐induced calcium fluxes, reactive oxygen species production, or mitochondrial alterations during OC differentiation are potential NLRP3 inflammasome activators in WT cells (26, 27). In addition, ATP and cellular debris from dying cells, including OCs, which have a short lifespan in cultures, may also activate this inflammasome.…”
Section: Discussionmentioning
confidence: 99%